2021
DOI: 10.33785/ijds.2021.v74i01.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the milk yield, milk composition and physico-chemical parameters of ghee in lactating crossbred cows

Abstract: The aim of this study was to investigate the effect of season, production status, stage of lactation, and parity on milk yield, milk composition and physico-chemical parameters of ghee in forty crossbred cows (CBCs). Milk samples were collected from individual animal during morning in both summer (May-August) and winter (November-February) season. The results revealed that milk yield was significantly influenced by the production status and lactation stage. The fat percentage was significantly affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Sharma et al [54] reported a significant seasonal influence on milk composition of crossbred cattle reared in the Sub-Himalayan Region of north India, with a significant decline in SNF and total solids during the summer season (April-June) when compared to the rainy season (July-September). In a study by Veena et al [55] with crossbred cattle from Punjab, north India, milk protein and SNF were lower during the winter season (November-February) than during summer (May-August). Another possible factor contributing towards altered milk yield and composition is water intake [54] as well as a change in diet composition.…”
Section: Milk Performance and Compositionmentioning
confidence: 90%
“…Sharma et al [54] reported a significant seasonal influence on milk composition of crossbred cattle reared in the Sub-Himalayan Region of north India, with a significant decline in SNF and total solids during the summer season (April-June) when compared to the rainy season (July-September). In a study by Veena et al [55] with crossbred cattle from Punjab, north India, milk protein and SNF were lower during the winter season (November-February) than during summer (May-August). Another possible factor contributing towards altered milk yield and composition is water intake [54] as well as a change in diet composition.…”
Section: Milk Performance and Compositionmentioning
confidence: 90%
“…The amount of milk produced per lactation by the CDC is primarily determined by their genotype, parity, season of milking, calving interval, stage of lactation, availability of feeds, environmental factors and disease incidence (Veena et al, 2021). Previous studies reported that the crossbred (F 1 ) cattle developed from indigenous ( Bos indicus ) cows by mating with exotic bulls ( Bos taurus ) performed better in Bangladesh (Hossain et al, 2021).…”
Section: Introductionmentioning
confidence: 99%